Fabrication and characterization of supported dual acidic ionic liquids for polymer electrolyte membrane fuel cell applications - Zakeri, M. (Elsevier B.V., 2018)
In this study, we proposed an innovative and versatile method for preparation of highly stable and conductive supported ionic liquid (IL) membranes for proton exchange fuel cell applications. Novel covalently supported dual acidic IL membranes were prepared by radiation induced grafting of 4-vinyl pyridine (4-VP) onto poly(ethylene-co-tetrafluoroethylene) (ETFE) film followed by post-functionalization via sequential treatments with 1,4-butane sultone and sulfuric acid to introduce pyridinium alkyl sulfonate/hydrogen sulfate moieties. The advantage of our approach lies in grafting polymers with highly reactive functional groups suitable for efficient post-sulfonation. The membranes displayed better swelling and mechanical properties compared to Nafion 112 despite having more than 3 times higher ion exchange capacity (IEC). The proton conductivity reached superior values to Nafion above 80 Â°C. Particularly, the membrane with ion exchange capacity of 3.41 displayed a proton conductivity of 259 mScmâ1 at 95 Â°C. This desired conductivity value is attributed to the high IEC of the membranes as well as dissociation of the hydrophobic ETFE polymer and hydrophilic pyridinium alkyl sulfonate groups. Such appealing properties make the supported IL membranes promising for proton exchange membrane fuel cells (PEMFC). Â© 2018 King Saud University